2018
DOI: 10.1002/asia.201701666
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Properties of meso‐Substituted Porphyrin Mesogens with Triazole Linkages and Peripheral Alkyl Chains

Abstract: Discotic mesogens P/n-M (n=12, 16, 18, M=2 H, Zn and Cu) bearing a porphyrin core, triazole linkages and peripheral 3,4,5-trialkoxybenzyl units have been synthesized by a click-chemistry approach. The thermal behavior, photophysical properties and morphologies of these compounds were investigated by polarized optical microscopy (POM), differential scanning calorimetry (DSC), XRD, UV and PL, SEM and TEM. These compounds can self-assemble into hexagonal columnar phases in their pure states and form organogels in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…The research group of Cheng [ 63 ] designed a click inspired synthesis of novel discotic mesogen bearing a porphyrin unit, a triazole linkage, and a peripheral 3,4,5-trialkoxybenzyl unit ( Scheme 32 ). Firstly, free-base porphyrin conjugates 151a–c were obtained by the CuAAC reaction between metal free tetraalkynylporphyrin 149 and benzyl azides 150a–c .…”
Section: Reviewmentioning
confidence: 99%
“…The research group of Cheng [ 63 ] designed a click inspired synthesis of novel discotic mesogen bearing a porphyrin unit, a triazole linkage, and a peripheral 3,4,5-trialkoxybenzyl unit ( Scheme 32 ). Firstly, free-base porphyrin conjugates 151a–c were obtained by the CuAAC reaction between metal free tetraalkynylporphyrin 149 and benzyl azides 150a–c .…”
Section: Reviewmentioning
confidence: 99%
“…Photophysical studies supported by density functional theory (DFT) calculations showed strong evidence of efficient energy transfer (~40%) between the porphyrin and fluorescein moieties [30]. The research groups of Cheng [31] and Serrano [32] used the porphyrin-propargyl derivative P26 to prepare porphyrin-based dendrimers peripherally functionalized with alkyl chains linked by triazolyl rings and exhibiting liquid crystal behavior. Both groups developed synthetic routes using porphyrin P26 as the starting reagent for the CuAAC reaction with azide derivatives 7a-d (Scheme 10).…”
Section: Scheme 1 Schematic Preparation Of Microporous Porphyrin-basmentioning
confidence: 99%
“…Cheng [31] prepared porphyrin derivatives P27a,b bearing four 1,2,3-triazole moieties with three terminal alkyl chains (n = 16 or 18) in each one of the meso positions that self-assembled into a columnar hexagonal packaging. When the chemosensorial ability of derivative P27b (n = 18) was evaluated in solution towards a series of metal(II) cations, that compound showed a selective emission quenching in the presence of Cu 2+ ions.…”
Section: Scheme 1 Schematic Preparation Of Microporous Porphyrin-basmentioning
confidence: 99%
See 1 more Smart Citation